Collaborative teaching environment system using think-pair-share technique / Nik Azlina bt Nik Mahmood @ Nik Ahmad - Nik Mahmood, Nik Azlina (2008)
There is a growing global interest in extending the field of study from stand-alone teaching environment to collaborative or cooperative teaching environment. In the light of the recent explosive growth of information technology, the platform for collaborative activities is focused more on producing the web-based platform. This research reflects on Think-Pair-Share technique used for collaborative communication in virtual classroom, where it can be applied among students during the teaching and learning process. ‘Think’ individually, discuss with a ‘pair’, then ‘share’ the ideas with the rest of class. CETLs for the short of Collaborative Environment for Teaching and Learning Science, is a web-based application which uses Active Server Pages (ASP) as the development backbone; allowing collaborative teaching and learning between teacher and students. Students can engage in group activities and also collaborate with teacher online. A built-in chat room supports collaborative dialogue. Students can work either individually or collaboratively with their partners as directed by the teacher to follow the think-pair-share technique. The teacher has the ability to articulate their choices and decisions about the content, assessment, coordination, and cooperation, as well as to engage in regular reflection about classroom performance; because all works will be evaluated by the teacher online, and the marks and feedback are given according to Think-Pair-Share activities. CETLs also provides few other elements for communications between teacher and students such as email, notes and assignment upload and download, in addition to bulletin board. This research also summarizes the three-tier client-server architecture as well as Rational Unified Process(RUP) used for CETLs development. Unit Testing and User Acceptance Testing (UAT) are conducted to identify the level of user acceptance towards the system, besides evaluating the CETLs’ perceive usefulness and perceive ease of use.